ANALISIS FAKTOR PENYEBAB SISWA/SISWI KELAS XII MEMILIH PROGRAM STUDI DI UNIVERSITAS TRIBUANA KALABAHI - Albion Selly; Mariam H. Selly; Ardi J.N. Mabilehi (SILABUS: Jurnal Ilmu dan Inovasi Pendidikan, 2025)
This research aims to determine the factors that cause someone to choose a study program option At Tribuana Kalabahi University,several variables are analyzed, namely Job Opportunities, Study Costs, Parental Influence, Personal Interests, Study Program Image . This research is quantitative research using descriptive methods explorative. The population in this study were Class XII SMA/SMK students in Regency Alor  the sample in this study was taken as many as 188 high school and vocational school students  XII which is in Alor district with sampling techniques done properly random. Data Which collected in study use technique spread questionnaire study to class XII students SMA/SMK in Alor District. Technique The data analysis used in this research is statistical analysis descriptive percentage. The research results show firstly , the main factor that has a significant impact on the decision of high school/vocational school students to choose Tribuana Kalabahi Universityias a place to continue their higher education is the availability of access or ease of location, with an influence level reaching 55%. secondly i, the Primary School Teacher Education Study Program (PGSD) dominates by receiving the highest support from respondents, reaching a percentage of 34%. third, /the employment opportunity factor has a significant influence, with 81% of respondents, the study cost factor also has a large impact, reaching a score of 77%. Parental influence is also quite significant, with 69%. Personal interest actors had a slightly smaller but still quite relevant role, with a score of 58%. The image of the study program, although still relevant, apparently has a lower influence compared to other factors, namely only 44%.